Development of a rat model of lymphedema and the implantation of a collagen-based medical device for therapeutic intervention - Nguyen, Dung; Dionyssiou, Dimitrios; Zaitseva, Tatiana S.; Zhou, Anna T.; Sue, Gloria; Deptula, Peter; Moroz, Maxim A.; Tabada, Peter; Rockson, Stanley G.; Paukshto, Michael V.; Cheng, Ming-Huei; Huang, Ngan F. (Frontiers in Cardiovascular Medicine, 2023)
Secondary lymphedema is a common condition among cancer survivors, and treatment strategies to prevent or treat lymphedema are in high demand. The development of novel strategies to diagnose or treat lymphedema would benefit from a robust experimental animal model of secondary lymphedema. The purpose of this methods paper is to describe and summarize our experience in developing and characterizing a rat hindlimb model of lymphedema. Here we describe a protocol to induce secondary lymphedema that takes advantage of micro computed tomography imaging for limb volume measurements and visualization of lymph drainage with near infrared imaging. To demonstrate the utility of this preclinical model for studying the therapeutic benefit of novel devices, we apply this animal model to test the efficacy of a biomaterials-based implantable medical device.